Análise da influência da altura da edificação e do vão livre de fachada em edifícios de múltiplos pavimentos em concreto pré-fabricado com pé direito duplo na fachada frontal da edificação - Garcia, Matheus Ferreira (Universidade Federal de São Carlos, 2024)
The aim of this project was to investigate the structural behavior of buildings assembled from precast concrete with double-height ceilings on the first floor façade. To this end, extensive numerical model simulations were carried out using TQS® software. In this way, variables such as the position and geometry of the columns, the free façade span and the number of floors of the building were parameterized in order to take into account all the project parameters. Therefore, the goal achieved at the end of this work was to establish correlations between the variables adopted and the behavior of the structure in relation to its global stability and its need for reinforcement. In this way, we sought to deepen our knowledge of behavior and propose design recommendations for the execution of this type of prefabricated building, which is being widely used in commercial and residential buildings today. Finally, qualitatively, it was found that buildings with larger façade spans were less expensive to manufacture, although they were more sensitive to the need for reinforcement in the façade columns.
Analysis of the influence of building height and facade clearance in multi-story prefabricated concrete buildings with double height on the front facade of the building
Keywords: Concreto pré-moldado; Edifícios comerciais; Projeto; Pé direito duplo; Estabilidade global; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS